2002
DOI: 10.1007/s00439-002-0812-5
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for differential S100 gene over-expression in psoriatic patients from genetically heterogeneous pedigrees

Abstract: Psoriasis is an inflammatory skin disorder characterised by keratinocyte hyper-proliferation and altered differentiation. To date, linkage analyses have identified at least seven distinct disease susceptibility regions (PSORS1-7). The PSORS4 locus was mapped by our group to chromosome 1q21, within the Epidermal Differentiation Complex. This cluster contains 13 genes encoding S100 calcium-binding proteins, some of which ( S100A7, S100A8 and S100A9) are known to be up-regulated in individual patient keratinocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 19 publications
1
52
0
1
Order By: Relevance
“…Similar to other autoimmune diseases, including psoriasis (35), RA (8), juvenile RA (36), and diabetes (37), the proinflammatory S100A8 and S100A12 proteins (calgranulins) were upregulated in PsA compared with controls. Increased protein expression of S100A8 has been reported in PsA synovium and serum, and levels correlated with PsA activity (38).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Similar to other autoimmune diseases, including psoriasis (35), RA (8), juvenile RA (36), and diabetes (37), the proinflammatory S100A8 and S100A12 proteins (calgranulins) were upregulated in PsA compared with controls. Increased protein expression of S100A8 has been reported in PsA synovium and serum, and levels correlated with PsA activity (38).…”
Section: Discussionmentioning
confidence: 72%
“…A recently described rodent model of psoriasis and PsA was also associated with very early increased expression of S100A8 (42), further implicating this gene in disease pathogenesis. Psoriasis pedigrees with linkage to PSORS4 had increased expression of S100 proteins (35), raising the possibility that the increased expression detected in PsA could be genetically determined, perhaps by a polymorphism that affects the transcription or message stability of these genes.…”
Section: Discussionmentioning
confidence: 99%
“…Psoriasis patients are at an increased risk of developing and dying of a cardiovascular event (7)(8)(9)(10)(11). A potential pathogenic role for MRP8/14 in psoriasis is supported by the finding that MRP8/14 genes are located within the psoriasis PSORS4 susceptibility region (12), and that serum and skin MRP8/14 levels are increased in psoriasis and psoriatic arthritis patients (13,14) and in psoriasiform mouse models (15)(16)(17). However the significance of MRP8/14 in psoriasis pathogenesis, including its contribution to increased cardiovascular risk, remains unclear.…”
Section: Introductionmentioning
confidence: 97%
“…S100A7 or "psoriasin" has been linked to psoriasis because of its up-regulation in this disease [252,253]. Although no direct role of S100A7 in melanoma has been described yet, in one study, significantly higher levels of S100A7 were found in the urine of melanoma patients compared to that of healthy patients [254].…”
Section: Other S100 Proteinsmentioning
confidence: 99%